2016
DOI: 10.11604/pamj.2016.25.17.10399
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality after breast cancer: cultural specificities of Tunisian population

Abstract: IntroductionWomen’s sexuality may be particularly affected after breast cancer. The objectives of this study were to evaluate the changes in sexual life after treatment of breast cancer in Tunisian women and to identify the influence of demographic and clinical factors on sexuality.MethodsWe recruited 50 patients who were in remission for at least 3 months after initial treatment of breast cancer. Sexuality and body image were evaluated using the Arabic version of the specific scale of breast cancer QLQ-BR23. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
29
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 36 publications
4
29
0
2
Order By: Relevance
“…The findings regarding optimal sexual health not reached in the women participating in our study (median = 2.34/5) are similar to those reported by Syrjala et al (28). Similarly, studies conducted in the United States, Tunisia, and Austria also coincide with the presence in their results of changes in its participants' sexual activity, like decreased sexual interest, arousal, orgasm, and sexual satisfaction, as well as problems in sexual functioning and appearance of vaginal dryness and vaginal pain (2,29,30,31).…”
Section: Discussionsupporting
confidence: 89%
“…The findings regarding optimal sexual health not reached in the women participating in our study (median = 2.34/5) are similar to those reported by Syrjala et al (28). Similarly, studies conducted in the United States, Tunisia, and Austria also coincide with the presence in their results of changes in its participants' sexual activity, like decreased sexual interest, arousal, orgasm, and sexual satisfaction, as well as problems in sexual functioning and appearance of vaginal dryness and vaginal pain (2,29,30,31).…”
Section: Discussionsupporting
confidence: 89%
“…For instance, Wang et al, showed that almost all patients reported a significant reduction in the frequency of sexual activities [21]. Moreover, Leila et al 's study on fifty Tunisian women with BC reported that more than half of them after cancer experienced a reduction in the frequency of sexual intercourses and reported sexual satisfaction [33]. A systematic review by Chang et al, demonstrated a reduced frequency of sexual relationships in women with BC after treatment [15].…”
Section: Discussionmentioning
confidence: 99%
“…About 81% of them showed less sexual sense/desire and 43% of them presented with dyspareunia. Furthermore, 42% of them had anxiety and 44% had depression which was significantly associated with body image (p<0.05) [25].…”
Section: Discussionmentioning
confidence: 96%
“…It also affected the sex life of their partners [9]. As young breast cancer patients are more sexually active, lack of sexuality plays an important role [25]. The intrapsychic capacity of females changes due to a sexual dysfunction that involves negative body image, fear of fertility loss, loss of femininity, absence of sexual interest, and shifts to a sense of sexual self [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation